Relationship between Clinical Features and Histopathologic Findings in Patients with Pulmonary Vein Stenosis - Mykychak, Y.; Kozhokar, D.; Yusifli, I.; Yachnik, O.; Zakharova, V.; Yemets, I. (Ukrainian Journal of Cardiovascular Surgery, 2019)
Pulmonary vein stenosis (PVS) is a rare but serious condition characterized by obstruction of extrapulmonary segments of pulmonary veins which leads to progressive pulmonary hypertension. Objective. In this study we aimed to determine relationship between clinical features and histopathologic findings in patients with PVS. Material and methods. We retrospectively reviewed 34 consecutive patients who underwent PV stenosis repair. Surgical wedge biopsy specimens were collected intraoperatively in 11 patients and reviewed using light microscopy. Results. Affected pulmonary veins in patients with primary PVS were characterized by diffuse stenosis extending into the lung parenchyma. In post-surgical group stenosis was found in a limited segment of pulmonary vein at its ostium. Microscopically, abnormal intimal proliferation was identified in both patient groups. Scaring was predominant finding in patients with post-surgical PVS. Conclusion. In patients with PVS, pathophysiological mechanism influences the severity and extent of clinical manifestations. A comprehensive understanding of this mechanism may improve results of the treatment.